Strategic Choices in Polygamous Households: Theory and Evidence from Senegal - Pauline Rossi (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2016)
This paper proposes a strategic framework to account for fertility choices in polygamous households. A theoretical model specifies the main drivers of fertility in the African context and describes how the fertility of one wife might impact the behavior of her co-wives. It generates predictions to test for strategic interactions. Exploiting original data from a household survey and the Demographic and Health Surveys in Senegal, empirical tests show that children are strategic complements. One wife raises her fertility in response to an increase by the other wife, because children are the best claim to resources controlled by the husband. This result is the first quantitative evidence of a reproductive rivalry between co-wives. It suggests that the sustained high level of fertility in Africa does not merely reflect women's lack of control over births, as is often argued, but also their incentives to have many children. This paper also contributes to the literature on household behavior as one of the few attempts to open the black box of non-nuclear families.
Keywords: C72; D13; J13; J16; O15; O55; 330; Fertility; Polygamy; Africa; Noncooperative models; Duration models